Anemia Heart Disease in a Patient with Suspected Non-Transfusion Dependent Thalassemia, a Case Report - Agustinus Alfred Gunawan; Rambu Farah Effendy (Green Publisher Indonesia, 2024)
Case Report. A female, 22 years old, came to the emergency room at Waikabubak General Hospital with complaints of weakness and pallor that had worsened since 1 week ago. Patients feel shortness of breath after heavy work, which improves after resting, nausea, and heart pounding. The patient has some previous medical history and familial history, Physical examination showed facies cooley appearance, short stature with anemic conjunctiva, icteric sclera, and hepatosplenomegaly. Laboratories showed microcytic hypochromic anemia with elevated liver enzymes. Peripheral blood smear showed microcytic anemia with anisocytosis and poikilocytosis with target cells. CXR showed cardiomegaly and USG showed hepatosplenomegaly. Echocardiography showed LV eccentric hypertrophy, LA dilatation, mild AR, mild MR, mild TR with a low probability of pulmonary hypertension, normal systolic function, grade I LV diastolic dysfunction, and ejection fraction 55,2%. This patient was treated with omeprazole injection, blood transfusion, oxygen supplementation, oral lisinopril, and bisoprolol. Over two weeks showed improvement in symptoms and laboratory. Discussion. The diagnosis is made from anamnesis, physical examination, and limited supporting examination. Determining the exact diagnosis, and management of the underlying disease and complication based on patient symptoms and simple laboratory results. Conclusion. Cardiac involvement in thalassemia is a major complication. Management of complications is difficult in limited resources facilities. Education and pre-marital screening are required to reduce the incidence of underlying disease.